Peran Warna Desain Interior terhadap Perasaan Tenang Pengunjung SPA “Martha Tilaar”: The role of colors psychology in interior design towards Spa's Visitors : Study case of Martha Tilaar - Monica, Agnes; Darmayanti, Tessa Eka (Program Studi Desain Interior Unikom, 2022)
The interior design of the Spa room is currently of particular concern in improving its quality as a support for the psychological recovery of visitors in order to provide a comfortable and quiet room, one of which is the consideration of the color of the space. Color is a significant element of the interior since a layer of paint may dramatically modify the interior, disguise design problems can even change the psychological state of the individual who is in the room and if the person is tired, color can